Public Safety Realignment in Twelve California Counties - Turner, Susan (RAND Corporation, 2015)
The study reported here focused on the flexibility that California granted counties in implementing constitutionally mandated and legislatively created public safety realignment-in particular, whether counties continued and expanded existing county corrections practices or used realignment as an opportunity to change from "business as usual."